Sustainable and Smart Cities: Nodes of confluence and research tendencies - Figueirôa-Ferreira, Victor Garcia; Borchers, Tatiane; Fernandes, Ricardo Augusto Souza (Revista Nacional de Gerenciamento de Cidades, 2021)
With the aim of identifying approximation points and gaps to be filled in efforts to relate research on smart and sustainable cities, this study made use of bibliometrics and scientometrics to materialize information retrieved in searches conducted in academic databases. Starting from the literature in both fields, it was sought to visualize from the quantitative data, the recent state of researches that have this objective, where it was analyzed that: (i) research that relates these fields is still incipient, and is on the rise; and (ii) there is still a technocratic prevalence and a detachment regarding theoretical advances. Both the quantitative results and the literature support these assertions, and in conjunction with the keyword clouds, one can better visualize viable opportunities on different research fronts.